Repercussions of energy efficiency, FinTech, industrialization, and technological advancements on climate change: evidence from G20 countries - Zhao, Hongyang; Arshad, Rimsha (Frontiers in Environmental Science, 2025)
Climate change poses an urgent challenge to both developed and developing economies, with varying degrees of vulnerability and institutional capacity. This study investigates the impact of energy efficiency, technological and financial innovations, industrial-economic development, and institutional quality on climate change effects (CCE), measured by ecological footprint, across G20 countries. Using panel data from 2000 to 2022, we apply Method of Moments Quantile Regression (MMQR), Dynamic Ordinary Least Squares (DOLS), and Fully Modified Ordinary Least Squares (FMOLS) to capture both distributional effects and long-run relationships. The results reveal that energy and technological innovations significantly reduce CCE in both groups, though the impact is more pronounced in developing economies. In contrast, financial technologies are positively associated with CCE in developing economies, suggesting that the expansion of digital infrastructure without green safeguards may exacerbate environmental degradation. Energy efficiency exhibits a rebound effect in these contexts, undermining its potential benefits. Institutional quality and industrial development, however, consistently demonstrate a mitigating effect on ecological footprint. These findings offer differentiated policy insights: while innovation and governance reforms are critical across all contexts, developing economies require stronger regulatory frameworks to align digital and industrial growth with climate objectives. The study contributes to the broader discourse on sustainable development by identifying context-specific levers for reducing environmental pressures in alignment with the Sustainable Development Goals (SDGs).